Corrigendum Corrigendum to: Management of Tricuspid Regurgitation: The Role of Transcatheter Therapies. Issue 1 (2020) - Taramasso, Maurizio; Calen, Christelle; Guidotti, Andrea; Kuwata, Shingo; Biefer, Hector Rodriguez Cetina; Nietlispach, Fabian; Zuber, Michel; Maisano, Francesco
No abstract available